Challenges in Establishing Agribusiness Ventures in India - R. Venkattakumar; P. Chandrashekara; B.S. Sontakki (Journal of Agricultural Extension Management, 2025)
Agri Clinics and Agri Business Centres (ACBAC) Scheme was launched in 2002 to supplement the efforts of the government extension system by transforming agricultural graduates as agripreneurs. Nevertheless, only about 30 per cent of the trained graduates could establish agribusiness ventures successfully. This necessitates delineation of challenges to be addressed. This study conducted through an ex post-facto research survey during 2011-12 identifies challenges in establishing and sustaining agribusiness ventures as perceived by agripreneurs. The results advocate strategies to refine the implementation of the scheme, so that the success rate in conversion of trained graduates as agripreneurs can be enhanced.